Evaluasi Usability Pada Sistem Website Absensi Menggunakan Metode SUS - Isnaeni Rachmawati; Resad Setyadi (Journal of Information System Research (JOSH), 2023)
Information technology (IT) is currently experiencing rapid development and is able to provide convenience such as solutions for organizations such as implementing a system at the Serayu Citanduy Water Resources Management Office, namely the field employee attendance website system. This system functions to monitor and provide services related to the field of employee attendance. However, there are still obstacles, namely the lack of attention to usability aspects, one of which is that there are still several features and buttons that have not been completed. Therefore, this study aims to evaluate usability related to the field employee attendance website system using the System Usability Scale (SUS) method. The SUS method is useful for assessing a system from a usability perspective by evaluating it as in this study. The research data was obtained by distributing questionnaires to 56 users. Before carrying out calculations using the SUS method, first calculate validation and reliability, validation of this questionnaire produces valid results and reliability, namely 0.613 means that it is reliable, so that research can run well. the level for the Value Scale is on a D scale with an average final score based on the calculation of the SUS method, namely 58.35 and the position of the last adjective branch is at the "ok" level. make improvements to improve usability such as developing by paying attention to the user interface, completing and selecting features on the button so that it functions properly and needs to be evaluated.